1995
DOI: 10.1007/bf02789001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of various nickel compounds in rat organs after oral administration

Abstract: In this study, eight kinds of nickel (Ni) compounds were orally administered to Wistar male rats and the distribution of each compound was investigated 24 h after the administration. The Ni compounds used in this experiment were nickel metal [Ni-M], nickel oxide (green) [NiO(G)], nickel oxide (black) [NiO(B)], nickel subsulfide [Ni3S2], nickel sulfide [NiS], nickel sulfate [NiSO4], nickel chloride [NiCl2], and nickel nitrate [Ni(NO3)2]. The solubilities of the nickel compounds in saline solution were in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 7 publications
0
19
0
2
Order By: Relevance
“…A distinct transfer of Nickel (significantly different than control) was observed in kidney and lung (Ishimatsu et al, 1995). A distinct transfer of Nickel (significantly different than control) was observed in kidney and lung (Ishimatsu et al, 1995).…”
Section: Distributionmentioning
confidence: 73%
See 1 more Smart Citation
“…A distinct transfer of Nickel (significantly different than control) was observed in kidney and lung (Ishimatsu et al, 1995). A distinct transfer of Nickel (significantly different than control) was observed in kidney and lung (Ishimatsu et al, 1995).…”
Section: Distributionmentioning
confidence: 73%
“…After oral administration of Nickel, no renal failure was detected (Koizumi et al 2005), the increase in urinary Nickel concentration occurred in a dose dependent manner, and soluble Ni compounds were excreted with urine within 72 hours after a single oral administration (Ishimatsu et al, 1995;Koizumi et al 2005;Janicka and Cempel, 2003). This is confirmed by Nielsen et al, (1993) who reported that up to 20 h after single oral administration of doses comparable to the human dietary intake, Nickel retention was highest in the kidneys.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…NiCl) and observed a 3-6 % excretion in the urine within 48 hours from administration, regardless of the administered dose. Ishimatsu et al (1995) showed that the GI absorption of Ni correlates with the water solubility of the administered Ni-containing substance. Wistar rats were administered a single dose of 10 mg Ni as metallic Ni, (green or black) Ni oxide, Ni subsulfide, Ni sulfide, Ni sulfate, Ni chloride or Ni nitrate.…”
Section: Other Exposuresmentioning
confidence: 99%
“…Prolonged exposure of rats to nickel in drinking water increased nickel levels in tissues and body fl uids; the highest level was found in the liver, followed by kidney Ï­ blood ÏŸ serum ÏŸ testes ÏŸ urine ÏŸ ovaries [73]. Oral ingestion of insoluble nickel compounds resulted in much lower intestinal absorption [74]. Inhalation of nickel carbonyl by animals increases the lung and body burden of nickel that is subsequently excreted, mainly in urine [23,75].…”
Section: Uptake Distribution Metabolism and Excretionmentioning
confidence: 99%